A Clinical and Epidemiological Study of Pityriasis Versicolor in Baghdad City - Abbas, Kholod; Mohammed, Luma K.; Hussein, Wajeeh N. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Pityriasis versicolor (PV) is a common and chronic superficial mycosis seen in all age groups and characterized by dyspigmented lesions caused by dimorphic lipophilic yeast. AIM: The aim of the study was to study the clinical aspects, prevalence, and demographic data of patients with PV in Baghdad City. MATERIALS AND METHODS: Total of 175 patients with PV attending the department of Dermatology at Al Imamein Al Kadhemein Medical City and Alkarama Teaching Hospital in Baghdad city from January 2019 to January 2020 were included in this study. Diagnosis was done clinically. Interviews with patients were done using a questionnaire designed by the researcher. RESULTS: From 175 patients with PV, there were 71 (40.6%) males and 104 (59.4%) females. The mean age was 23.97 ± 10.25 years. The majority of cases 71 (40.6%) were 21–30 years. Eighty-one (46.3%) patients were presented from April to June. Itching presented in 21.7% of patients. The majority of patients (48.6%) presented with hyperpigmented type. Neck was the most common site to be involved in 101 patients (57.7%). CONCLUSION: The most common age group affected was 21–30 years. Females were commonly affected. Peak incidence was observed in April–July months. Neck was the most common site affected. Hyperpigmented type is more commonly presented type.